Gender differences in the relative age effect among US Olympic Development Program youth soccer players - Vincent, J.; Glamser, F. D. (Journal of Sports Sciences, 2006)
A large body of research has shown that a disproportionate number of elite youth male soccer players competing in agesegmented competition are born early in the selection year. The advantage of being born early in a cohort has been termed the``relative age effect``. Although there has been an exponential growth in women`s soccer, few studies have examined the relative age effect in female youth soccer. This study compared the relative age effect of 1344 female and male youth soccer players considered by the US Olympic Development Program (ODP), in 2001, to be the most talented soccer players born in 1984. The birth dates were taken from the women`s state and regional ODP, and national team rosters, and were analysed using basic descriptive statistics and chi-square tests. Results revealed only a marginal relative age effect for female ODP regional and national team players and no relative age effect for female ODP state team players. In comparison, a strong relative age effect was found in male state, regional and national team players. The results suggest that there are gender differences in the relative age effect of 17-year-old elite female and male soccer players. The gender differences may be explained by a complex interaction of biological and maturational differences with socialization influences.